Platinum Complexes from C–H Activation of Sterically Hindered [C^N] Donor Benzothiophene Imine Ligands: Synthesis and Photophysical Properties - Anderson, Craig M.; Coffey, Belle; Morales, Leslie; Greenberg, Matthew W.; Norman, Matthew; Weinstein, Michael; Brown, Garrett; Tanski, Joseph M. (ACS omega, 2020)
Primary amines and benzothiophene-3-carboxaldehyde were reacted to give four large, bulky imine ligands. These imine ligands were reacted with a tetramethyl platinum dimer and by heteroatom-assisted C-H activation, both monometalated compounds and bismetalated compounds were synthesized. In all cases, five-membered platinacycles were formed. The compounds were characterized by NMR spectroscopy, and one bismetalated compound was characterized by single-crystal X-ray diffraction. The UV-vis absorption and emission spectra and the excited-state lifetimes were recorded for these complexes. Density functional theory (DFT) and time-dependent-DFT calculations were performed to aid in the assignment of the absorption and emission spectra of the newly synthesized complexes.